Philosophy in the Condition of Modernism (Springer International Publishing, 2018)
Produced on the fringes of philosophy and literary criticism, this book is a pioneering study which aims to explicitly address and thematize what may be called a "critical philosophy in the condition of modernism". Its most important and original contribution to both disciplines is a self-conscious reflection on possible modes of writing philosophy today, and a systematic comparison with what happened in literary modernism at the beginning of the twentieth-century. The volume is divided into six sections, where internationally renowned scholars discuss such pressing topics as the role of an unreliable narrator in a major philosophical treatise, the different mediums of art-production and how these impact on our perception of the Work itself, the role of narrative in animal ethics and the filmic adaption of a Modernist classic. .